A Systematic Climatology Report of Aviation Weather Hazards on Yangon Airport Region - Oo, Kyaw Than; Jonah, Kazora; Oo, Kyaw Lwin (Journal of Multidisciplinary Research Advancements, 2023)
The primary goal of the research was to examine the aviation climatology analysis of the thunderstorms and fog on study area based on the statistical evaluation of the meteorological station's observation data. Weather is a critical factor in aviation, profoundly affecting aircraft operations and safety. The global aviation industry, with a staggering economic impact of $3.5 trillion and contributing 4.1 percent of global GDP, relies heavily on weather data and analysis. Study used METAR data from Myanmar's Yangon International Airport (VYY). Analysis of METAR, flight delay and accident data revealed that the influence of thunderstorms and fog might have had a direct or indirect impact on most accidents over study area. The frequency analysis method were primarily used in this study and the new method of fog event analysis came out. The two meteorological occurrences, thunderstorm rain (TSRA) and fog (FG), are also high frequency at VYY in a year and TSRA is a larger risk than FG for aviation operation due to its relative other weather phenomena. The July is the maximum TSRA occurrence month and total annual frequency analysis revealed that TSRA days are becoming more common year by year because of study. In addition, the total number of days with fog varies from 23 to 91 per year, with the most frequent time of day being between 2300 and 01:00 UTC. The conditions where the fog was most likely to form were those when the minimum temperature fell between 16 and 27 °C (liquid fog). The study raises a new question and a new possibility for viewing climatology from a new perspective. The insights gained from this report can contribute to the development of tailored weather forecasting and alert systems for pilots and airport personnel. Further deep study for systematic prediction of each hazards are leaved for future work.